AFSIM's pseudo-realtime hybrid simulation software design. (October 2022) - Thompson, J Scott; Hodson, Douglas D
Simulation approaches generally fall into two categories: discrete time or discrete event. For military modeling and simulation needs, the two approaches typically align with virtual simulation, which implies human interaction with the simulation program, and constructive simulation, which implies no human interaction. The Air Force Research Laboratory develops and distributes AFSIM (Advanced Framework for Simulation, Integration, and Modeling) to a user community that uses both virtual and constructive simulation. This paper documents the software design and primary algorithms that provide AFSIM's support for both modes, which is termed a hybrid simulation.